Effects of lesion size on the 30-month clinical performance of restorations with bulk fill and a regular nanofilled resin composite in noncarious cervical lesions - Correia, Ayla Macyelle de Oliveira [UNESP]; Jurema, Ana Luiza Barbosa [UNESP]; Bresciani, Eduardo [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP] (Springer Nature, 2023)
Objective: The aim of this double-blind, randomized trial was to evaluate the influence of the occlusogingival distance (OGD) in noncarious cervical lesions (NCCLs) on the clinical performance of a regular bulk-fill resin composite and a regular nanofilled resin composite. Materials and methods: One hundred and forty NCCLs in 77 participants were randomly divided into four groups (n = 35), according to OGD (1.5 mm ± 10% or 3 mm ± 10%) and resin composites (Filtek Bulk Fill Posterior [B] or Filtek Z350 XT [C]), namely: 1.5 mm-B, 1.5 mm-C, 3 mm-B, and 3 mm-C. The restorations were bonded using a two-step self-etch adhesive (Clearfil SE Bond), applied following the manufacturer’s instructions. Restorations were polished 1 week after placement. Two experienced and calibrated examiners evaluated the restorations using modified US Public Health Service criteria at baseline (7 days) and after 6, 12, 18, 24, and 30 months. Statistical analyses were carried out using Kruskal–Wallis, Friedman’s repeated measures analysis of variance, and the Wilcoxon signed rank test (α = 0.05). Results: After 30 months, the recall rate was 94.2%. Eight restorations were lost (3 for 1.5 mm-C, 2 for 1.5 mm-B, 1 for 3 mm-C, and 2 for 3 mm-B). All groups resulted in a significantly worse marginal discoloration and surface texture at 30 months in comparison with the baseline (1 week). No significant difference was found for the other parameters. Conclusion: The restorations performed with both resin composites produced clinically acceptable restorations. The OGD of NCCLs did not influence the clinical performance of restorations. Clinical significance: The OGD of NCCLs did not have a significant effect on the clinical performance of a regular bulk-fill and nanofilled restorations. Both materials showed a very good performance on 30-month evaluation.
Keywords: Bulk-fill; Composite resins; Incremental filling; Noncarious cervical lesions; Randomized controlled trial